GANGGUAN FUNGSI PARU PADA POLISI LALU LINTAS - nendyah roestijawati; Indah Rahmawati; Dwi Arini Ernawati; Khairunnisa Puspita Ayu (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
PULMONARY FUNCTION DISORDERS IN TRAFFIC POLICE Nendyah Roestijawati1), Indah Rahmawati2), Dwi Arini Ernawati1), Khairunnisa Puspita Ayu3) 1)Departemen Kesehatan Masyarakat dan Kedokteran Komunitas 2)Departemen Ilmu Penyakit Dalam 3)Jurusan Kedokteran Fakultas Kedokteran Universitas Jenderal Soedirman Email : nendyahr@yahoo.com Traffic policemen are professions that are susceptible to pulmonary function disorders due to exposure to air pollutants. Other factors that can cause lung function disorders are age, sex, body mass index, length of work, duration of work, smoking and using personal protective equipment habits. The study aims to determine pulmonary function disorders in the traffic police of the Banyumas District Police and the factors that influence them. Cross sectional study design wa used with 50 subjects based on inclusion and exclusion criteria. Impaired pulmonary function was measured by spirometry and other variables were collected using a questionnaire by interview and measurement of body weight and height. Data analysis used the Fisher and Kolmogorov Smirnov test. The results of the study found 82% of subjects experienced a restriction disorder. Factors associated with impaired pulmonary function are body mass index, smoking and using personal protective equipment habits (p <0.05), while factors of age, sex, length and duration of works are not related to impaired lung function (p> 0.05). Keywords: pulmonary function disorder, policemen, spirometry